To find the equation of the reflection of \( y = 3x \) in the x-axis, we replace \( y \) with \( -y \). This gives us:
\[ -y = 3x \]
To isolate \( y \), we multiply both sides by -1:
\[ y = -3x \]
Now, let's look at the options provided:
- \( y = - (3^x) \)
- \( y = x^3 \)
- \( y = 3^{-x} \)
- \( y = \log_3 x \)
None of these options exactly matches \( y = -3x \). It's possible that there might be a misunderstanding. However, based on the process, the correct reflection of the line \( y = 3x \) across the x-axis is \( y = -3x \), which does not appear in the answer options.
Since none of the provided options are correct based on the expected reflection of the equation \( y = 3x \), if you have to select one from the options, please clarify or double-check the context of the question or the options provided.